Dead broke [large type] - Chapman, Vannetta (Chapman, Vanetta. Agatha's Amish B&B ;, 2021)
"Why would someone kill Nathan King? The peace of a perfect November afternoon is shattered when Agatha hears the frantic bleating of goats across the river from her B&B. Agatha kayaks over with retired detective Tony and two guests - Bishop Henry and his wife Emma. They find the goats huddled together in a terrified group and Nathan lying face up, lifeless eyes staring at the Texas sky. Then one of Agatha's guests goes missing. She delves into Joey's past and learns he was dead broke, so what was he doing vacationing at her B&B? And why was he pretending to be Amish? Most importantly, did Joey have anything to do with Nathan's death? Agatha and Tony are at a dead end before the investigation has properly begun, but this time they receive help from unexpected places. Bishop Henry has a gift, and he's no longer afraid to use it, even if doing so may put them all in danger as they work together to catch a killer."--